The eschatological perspective of the world in the philosophical and logical thought of antiquity and modern times: ontological and gnoseological challenges - Vitiuk, Iryna; Kondratiuk, Yuliia; Mosienko, Oleksandr (Вісник гуманітарних наук, 2026)
This article conducts a comparative analysis of ancient and modern eschatological models to explain the patterns behind contemporary ontological challenges. The study justifies revising the "end of the world" category as a tool to overcome existential anxiety and develop strategies for sustainable development amidst the current civilizational breakdown. Methods. A comparative-historical method contrasts ancient cyclical paradigms with modern linear models. A systemic approach treats eschatology as a holistic ontological category. Deconstruction of the idea of progress identifies the origins of modern catastrophism, while hermeneutic analysis of pre-Socratic, Platonic, and Cartesian works reveals the genetic links between classical doctrines and modernity. Results. It is proven that ancient thought transformed the mythological "end of the world" into an ontological regularity where the finale serves as a natural stage of cosmic renewal. Ancient cyclism (Heraclitus, Stoics) is revealed as a philosophical prototype for modern sustainable development. Conversely, the modern linear model and subject-object relations shifted the human role from passive observer to an active, transformative force. Conclusions. The study substantiates the concept of a "responsible eschaton" – a 21st-century synthetic model integrating ancient ontological limits with modern subject ethics. Overcoming existential anxiety requires combining ancient "calm finalism" with awareness of technogenic responsibility. This approach transforms eschatological expectations into a methodological basis for managing global risks (AI, ecological collapse), functioning as an ethical regulator that restores planetary unity and defines the limits of nature interference.